Right Atrial Appendage Aneurysm in a Newborn Diagnosed with Fetal Echocardiography - Bornaun, Helen (Case Rep Pediatr, 2016)
Right atrial appendage aneurysm is a very rare condition which can be asymptomatic or can cause arrhythmia or life-threatening thromboembolism. We report a case of newborn with right atrial appendage aneurysm who was diagnosed with fetal echocardiography. Anticoagulant therapy was applied to prevent thromboembolism and he is still going on follow-up without any complaint.